Development and mechanism study of functional fermentation media for reducing alkaloid content in cigar tobacco leaves - Wanrong Hu; Li Liu; Jiabao Zhang; Quanwei Zhou; Zhongrong Jiang; Yun Jia; Qianying Zhang; Dongliang Li (Chemical and Biological Technologies in Agriculture)
Abstract Background Elevated alkaloid levels in tobacco leaves can cause significant irritation and a pronounced bitterness. Fermentation is a well-recognized strategy to reduce alkaloid content. However, its effectiveness is influenced by the choice of fermentation media. The limited variety of available media complicates the ability to meet the specific formulation requirements of cigar products. Consequently, there is a need to develop additional media to tailor formulations that optimize fermentation outcomes. Results The fermentation media developed in this study were primarily composed of compounds including chlorogenic acid, liquiritin, schaftoside, and ganoderic acid. The fermentation of cigar tobacco leaves with a medium led to a reduction in total nitrogen and alkaloid levels, while simultaneously enhancing both total sugar and reducing sugar contents. Specifically, compared to the control group, the alkaloid content in tobacco leaves treated with the medium decreased by 9.58–19.06%. Furthermore, the addition of the medium resulted in an increase in aroma compounds, while the levels of unsaturated fatty acids decreased by 7.14–24.66%. The medium also elevated the contents of characteristic aroma components, including 3-hydroxy-5,6-epoxy-β-ionol, megastigmatrienone, β-dihydroionone, dihydroactinidiolide, and sclareolide. Additionally, the introduction of the medium altered the bacterial and fungal community structures within the cigar tobacco leaves. It also facilitated the proliferation of functional microorganisms such as Acinetobacter, Enterobacter, Pseudomonas, Wickerhamomyces, and Wallemia. Correlation analysis indicated a positive relationship between the enrichment of these functional microorganisms and the increased levels of aroma compounds, such as 3-hydroxy-5,6-epoxy-β-ionol. From a sensory perspective, the incorporation of the medium reduced irritation and undesirable odors in cigar tobacco leaves, while enhancing the sweetness and richness of the aroma. Conclusions The specialized media developed in this study represent an innovative approach to optimizing cigar tobacco fermentation. This method utilizes unique raw materials and bioactive compounds to coordinate microbial activity, reduce alkaloid level, enhance aroma components, and improve sensory attributes. From an application standpoint, these media could be seamlessly integrated into cigar processing lines to enhance product quality with minimal modifications to existing equipment. The findings of this study offer novel perspectives on the reduction of alkaloid content in tobacco and the advancement of functional media. Graphical Abstract